1996
DOI: 10.1002/1529-0131(199604)9:2<97::aid-anr1790090205>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy predicting outcome among fibromyalgia subjects

Abstract: Objectives. This study examined whether pretreatment self‐efficacy and pre‐ to post‐treatment changes in self‐efficacy predict post‐treatment tender point index, disease severity, pain, and physical activity. Methods. One hundred nine subjects with fibromyalgia were assessed before and after a 6‐week training intervention. Measures included tender point index, physician ratings of disease severity, the visual analog scale for pain, the Physical Activities subscale of the Arthritis Impact Measurement Scales, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 17 publications
(17 reference statements)
4
71
1
4
Order By: Relevance
“…For instance, in studies exploring the effectiveness of CBT-based treatment of depression [14] and panic disorder [25], treatment outcomes were more favourable for individuals with higher baseline self-efficacy. Similar findings have been found with respect to treatments for fibromyalgia patients [26]. In contrast, Eden and Aviram [27] found that a reemployment program increased the chance of finding work only for individuals with low levels of general self-efficacy.…”
Section: Influence Of Self-efficacy On Treatment Successsupporting
confidence: 70%
“…For instance, in studies exploring the effectiveness of CBT-based treatment of depression [14] and panic disorder [25], treatment outcomes were more favourable for individuals with higher baseline self-efficacy. Similar findings have been found with respect to treatments for fibromyalgia patients [26]. In contrast, Eden and Aviram [27] found that a reemployment program increased the chance of finding work only for individuals with low levels of general self-efficacy.…”
Section: Influence Of Self-efficacy On Treatment Successsupporting
confidence: 70%
“…The ASES has been successfully used in other studies of persons diagnosed with FM. [53][54][55][56][57] …”
Section: Self-efficacymentioning
confidence: 99%
“…In addition, higher pretreatment self-efficacy scores significantly predict higher posttreatment physical activity. Larger changes in self-efficacy significantly predict higher posttreatment levels for physical activity, and lower posttreatment levels for pain and disease severity (36).…”
Section: Effects Of the Interventions On The Sleep Measurementioning
confidence: 99%